An efficient merging of DBU/enolate and DBU/benzyl bromide organocycles for the synthesis of alpha benzylated 1-indanone derivatives. (13th April 2022) - Singh, Shikha; Trivedi, Laxmikant; Vasudev, Prema G.; Passarella, Daniele; Negi, Arvind S.
Abstract : 1, 8-Diazabicyclo[5.4.0]undec-7-en (DBU) mediated synthesis of α-benzylated 1-indanones via DBU/enolate and DBU/benzyl bromide organocycles under mild reaction conditions. Abstract : The merging of dual organocycles of the bicyclic amidine base 1, 8-diazabicyclo[5.4.0]undec-7-en (DBU) was demonstrated for the synthesis of alpha-benzylated 1-indanones. A highly reactive enolate intermediate was formed in the presence of DBU, which reacted with DBU/benzyl bromide salt to afford the product at 50 °C temperature. This simple and straightforward transformation using safer DBU reagent with easily available substrates and excellent yield provides a better alternative to the previously reported methods that required pyrophoric, costly reagents and high or very low-temperature reaction conditions. CIMAP Communication number: CIMAP/PUB/2022/3.